PENERAPAN JARINGAN SENSOR UNTUK MEMINIMALISIR KRIMINALITAS DI KABUPATEN KUBU RAYA: PERSPEKTIF HUKUM PIDANA - Astono, Agustinus; Muyassar, Ya' Rakha (Justitia et Pax, 2024)
This research is urgent to maintain public order and security in Kubu Raya Regency, one of the areas with the highest crime rate in West Kalimantan. According to Aipda Ade, Kasubbag Penmas Polres Kubu Raya, frequent crimes in 2023 include motorcycle theft, grand theft, and theft with violence. Therefore, effective measures are needed to overcome this recurring crime problem. The research problem formulated is why the application of sensor networks is needed to minimize crime in Kubu Raya Regency. This research uses a normative legal method with a statutory approach, analyzing community behavior and prevailing norms. Data were collected from primary and secondary legal materials, including laws and official documents from the Kubu Raya Regional Government and Kubu Raya District Police. The conclusion of this research is that sensor networks can detect suspicious movements or activities, such as the movement of unknown individuals or vehicles. With real-time information provided by sensor networks, security forces can respond to criminal activity quickly and appropriately. The application of sensor networks is an innovative and effective solution to overcome security problems in Kubu Raya Regency. This system is expected to reduce the crime rate and increase the sense of security and comfort for the community in their daily activities.